On the large-scale radiative cooling induced by tropical cyclone activity - Gabriel A. Rios; Gabriel A. Vecchi; Wenchang Yang (Proceedings of the National Academy of Sciences, 2026)
Tropical cyclones (TCs) are among the most energetic phenomena in the climate system. Given their energetic nature, TCs induce upscale effects on the climate system, although these effects have not been extensively assessed. Understanding the influence of TCs on climate is important given the expected changes in TC activity with a warming climate. In this study, we provide evidence that TCs induce large-scale radiative cooling. We compare the climates of a coupled global climate model in two configurations: a control configuration with Earth-like TC activity and a perturbed configuration where TC activity is reduced by suppressing wind-induced surface heat exchange in areas with TC-like conditions. By comparing climate states, we find a reduction of incoming top-of-atmosphere radiation with more TC activity, largely in the subtropics. Globally, TC activity drives increases to longwave emission that outweigh increases to absorbed solar radiation. We show that decreases in sea surface temperature occur as an adjustment to TC-induced perturbations, coincident with increases in longwave emission caused by a drying of the free troposphere and a reduction in high cloud fraction. The results demonstrate the role of TCs in organizing convection, suggesting that TCs play a role in modulating climate sensitivity and large-scale energy transport.